Effective field theory of fluctuating wall in open systems: from a kink in Josephson junction to general domain wall - Fujii, Keisuke; Hongo, Masaru (SciPost physics, 2022)
SciPost Journals Publication Detail SciPost Phys. 12, 160 (2022) Effective field theory of fluctuating wall in open systems: from a kink in Josephson junction to general domain wall
Gesehen am 31.05.2022